Perbandingan Sistem Pengukuran Kinerja Perusahaan - Freddy Simbolon (Bina Nusantara University, 2015)
Corporate performance is a measure of the level of success in managing resource company to create value for share holders and stakeholders. Many of the company's performance measurement system can be used, but the future of performance measurement systems are no longer limited only to the measurement of financial performance, yet more comprehensive and integrated to non-financial aspects of the coverage of measurements on the internal and external environment. There are three performance measurement system that meets these criteria is the BSC, IPMS, and Prism. This research method is using descriptive method of analysis. This study aims to assess the three systems that get the best system to choose. All three systems have advantages and disadvantages, so the best option is a performance measurement system compatibility with the company'scondition and capabilities of decision makers.